2012
DOI: 10.1177/1352458512455958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep disorder treatment on fatigue in multiple sclerosis

Abstract: Treatment of sleep disorders can improve fatigue and other clinical outcomes in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 36 publications
3
38
3
2
Order By: Relevance
“…However, our results revealed that the decrease in general fatigue among patients in the cooling group (Δ = -6.0, effect size = 2.8) is higher than that reported by Côté et al [28] in PwMS undergoing treatment for sleep disorders (Δ = -3.1, effect size = 0.82). This result suggests that physical activity has a positive impact on general fatigue and highlights the potential influence of body cooling on PwMS during physical activity.…”
Section: Discussioncontrasting
confidence: 55%
“…However, our results revealed that the decrease in general fatigue among patients in the cooling group (Δ = -6.0, effect size = 2.8) is higher than that reported by Côté et al [28] in PwMS undergoing treatment for sleep disorders (Δ = -3.1, effect size = 0.82). This result suggests that physical activity has a positive impact on general fatigue and highlights the potential influence of body cooling on PwMS during physical activity.…”
Section: Discussioncontrasting
confidence: 55%
“…Two independent open follow-up studies have demonstrated an improvement of MS-related fatigue by the treatment of underlying sleep disorders [22,23], but we need randomized controlled studies in order to confirm these findings. Two months after treatment with cortisone 1 g/day for 3 days, the hypothalamic lesions were diminished and the MSLT showed a mean sleep latency of 17.4 min and only one SOREMP.…”
Section: Future Research Directionsmentioning
confidence: 93%
“…In both studies, the follow-up studies showed that sleep medical treatment started subsequently improved fatigue [22,23].…”
Section: Sleep-related Breathing Disordersmentioning
confidence: 97%
“…Here, we use data obtained from the baseline evaluation and first night PSG results. Further details of this study are described elsewhere (Kaminska et al, 2011;Côté et al, 2013). The Institutional Review Board of the participating institution approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…OSAH was defined by an apnea-hypopnea index (AHI) of ≥ 15 events per hour of sleep (Kaminska et al, 2011;Côté et al, 2013).…”
Section: Objective Sleep Datamentioning
confidence: 99%